2009
DOI: 10.1017/s0033291709991243
|View full text |Cite
|
Sign up to set email alerts
|

Using the Cambridge Neuropsychological Test Automated Battery (CANTAB) to assess the cognitive impact of electroconvulsive therapy on visual and visuospatial memory

Abstract: Patients receiving ECT displayed a range of visual and visuospatial deficits over the course of their treatment. These deficits were most prominent for tasks dependent on the use of the right medial temporal lobe; frontal lobe function may also be implicated. The CANTAB appears to be a useful instrument for measuring the adverse cognitive effects of ECT on aspects of visual and visuospatial memory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
44
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 43 publications
7
44
1
Order By: Relevance
“…It has also been used successfully to detect deficits in visuospatial short-term memory in neurosurgical patients with temporal or frontal lobe excision (Owen et al, 1995). Specifically, Falconer et al (2010), in a study involving Electroconvulsive Therapy (ECT), showed that the CANTAB can assess the cognitive impact of ECT on visual working memory.…”
Section: Cognitive Assessmentmentioning
confidence: 99%
See 2 more Smart Citations
“…It has also been used successfully to detect deficits in visuospatial short-term memory in neurosurgical patients with temporal or frontal lobe excision (Owen et al, 1995). Specifically, Falconer et al (2010), in a study involving Electroconvulsive Therapy (ECT), showed that the CANTAB can assess the cognitive impact of ECT on visual working memory.…”
Section: Cognitive Assessmentmentioning
confidence: 99%
“…Since the CANTAB is sensitive to brain dysfunctions in frontal and temporal regions, it is highly appropriate for assessing cognitive functions, especially in studies involving passage of electrical current on the frontal and temporal regions, by means of bilateral electrodes (Falconer, Cleland, Fielding, & Reid, 2010). Considering that our study involves applying direct current stimulation to the brain, we decided to use this battery.…”
Section: Cognitive Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Falconer et al (2010) used computerized neuropsychological testing and found signifi cant impairments in visual and visuospatial memory during, and in the week following ECT (Falconer et al, 2010). Most impairments resolve within one month following ECT; however, impairment remained in some domains (e.g.…”
Section: What Are the Side Effects?mentioning
confidence: 99%
“…The commonest complains from patient post-ECT includes retrograde amnesia and loss of autobiography memory 31 . Amnesia episode may last from 1 to 6 months after the end of ECT sessions, but there is no impairment of acquisition and retention of new memories 34 .Another author's indicated that memory problems could be solved after a one-month intervention 35 .Fraser et al observed that memory deficits caused by ECT usually last for less than six months 36 . Apart from most of the patients returning to their previous cognitive status, few still suffers from permanent drawbacks in their memory 29 .…”
mentioning
confidence: 99%